Food and Nutrition Security of Selected Farm Households of Sonipat and Karnal Districts in North India. Issue 6 (2nd November 2019) - Punia, Anusha; Kaushik, Sushma
ABSTRACT: Food is essential to be alive, no one can pretend when a natural disaster will sweep out all crop area, which perhaps by flood, drought and other irregularities in weather leads to loss of production, therefore, food is necessary to feed the population during these conditions. The present study was conducted in two districts of Rohtak division and data were collected in September, 2016–April, 2017. Two districts viz. Sonipat and Karnal were selected randomly and by selecting one block from each selected district and two villages from each of the selected blocks at random. From the selected four villages a sample of 300 respondents, i.e. 75 small and marginal farm families from each village was drawn at random to assess the status of food and nutrition security of small and marginal farm families. From 300 (150, i.e. small-87, marginal-63 from Sonipat district and 150, i.e. small-116, marginal-34 from Karnal district) were selected randomly. Results of the study revealed that 69.7per cent of farm families had food mainly from their own farm production, majority (67.0%) of farm families never faced any food scarcity. Regarding nutrition security, cereals and milk and milk products consumed on daily basis in both the districts and majority (81.3%) of children and more than half (56.0%) of women had normal body mass index.